Partisipasi Tokoh Masyarakat dalam Kewaspadaan Penyalahgunaan Narkotika - Pratama, Andika; Husin, Azizah (Journal of Nonformal Education and Community Empowerment, 2018)
This study aims to determine the participation of public figures in the vigilance of narcotics abuse. This type of research is descriptive quantitative. Data collection methods used were observation, questionnaire and documentation. Population of community leaders in Timbangan village amount of 205 and was taken sample 65 people with purposive sampling technique. The results showed that the participation of public figures in the vigilance of narcotics abuse is high. The form of participation of public figures in the vigilance of narcotics abuse is involved in the socialization activities of narcotics abuse, reporting to the authorities regarding narcotics abuse cases, involved in religious activities as strengthening the character, and taking an active role in advising the danger of narcotics abuse to the community or law enforcement / BNN. As a conclution that the community leaders already have high awareness and awareness about the dangers of drug abuse.